2005
DOI: 10.1124/jpet.105.096792
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of (E)-N-(4-Fluorobut-2-enyl)-2β-carbomethoxy-3β-(4′-tolyl)nortropane (LBT-999) as a Highly Promising Fluorinated Ligand for the Dopamine Transporter

Abstract: In the aim to develop an efficient fluorinated probe for positron emission tomography (PET) exploration of the dopamine transporter (DAT), we studied several in vitro and in vivo characteristics of the phenyltropane derivative (E)-N-(4-fluorobut-2-enyl)-2␤-carbomethoxy-3␤-(4Ј-tolyl)nortropane (LBT-999). In vitro on rat striatal membrane, [3 H]LBT-999 bound to a single site with a K d of 9 nM, B max of 17 pmol/mg protein, and a very high selectivity for the DAT [IC 50 for 1-{2-[bis-(4-fluorophenyl)-methoxy]ethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 35 publications
2
31
1
Order By: Relevance
“…One of the presynaptic functions is the dopamine reuptake mediated by dopamine transporter (DAT), a membrane-bound protein. A number of radioligands for in vivo DAT imaging have been developed for positron emission tomography (PET), such as [ 11 C]cocaine [1], [ 11 C]WIN35,428 (CFT) [2,3], [ 11 C]b-CIT (RTI-55) [4], [ 11 C] b-CIT-FE [5], [ 11 C]D-threo-methylphenidate [6], [ 18 F]FECNT [7], [ 11 C]Altropane [8], [ 11 C]PE2I [9] and most recently [ 11 C]LBT-999 [10]. Most of them are analogs of cocaine and have some degree of affinity for the serotonin transporter.…”
Section: Introductionmentioning
confidence: 99%
“…One of the presynaptic functions is the dopamine reuptake mediated by dopamine transporter (DAT), a membrane-bound protein. A number of radioligands for in vivo DAT imaging have been developed for positron emission tomography (PET), such as [ 11 C]cocaine [1], [ 11 C]WIN35,428 (CFT) [2,3], [ 11 C]b-CIT (RTI-55) [4], [ 11 C] b-CIT-FE [5], [ 11 C]D-threo-methylphenidate [6], [ 18 F]FECNT [7], [ 11 C]Altropane [8], [ 11 C]PE2I [9] and most recently [ 11 C]LBT-999 [10]. Most of them are analogs of cocaine and have some degree of affinity for the serotonin transporter.…”
Section: Introductionmentioning
confidence: 99%
“…) is a tropane derivative with high affinity for the DAT (radioligand equilibrium dissociation constant [K D ], 9.15 nM) (6), and similarly to PE2I, LBT-999 is of potential interest for imaging the DAT in the striatum and extrastriatal regions (7). LBT-999 has been labeled with both 11 C and 18 F (8-10).…”
Section: (2s3s)-methyl 8-((e)-4-fluorobut-2-en-1-yl)-3-(p-tolyl)-8-amentioning
confidence: 99%
“…Some studies identified efficient radioligands and isotopes currently used to explore the dopamine transporter (DAT) because this molecular target is involved in numerous neurological diseases such as Parkinson's disease in humans. In their study, Wang et al (2007) used the 18 F-FP-CIT, a radiotracer that binds specifically to DAT, whereas Chalon et al (2006) used the 11 C-LBT-999 to investigate the DAT variations in baboons. Minuzzi et al (2006), however, reported that several usual radioligands failed to bind to DAT in the pig brain, although they revealed the presence of DAT in rat, ferret, monkey and human brains.…”
mentioning
confidence: 99%